1979
DOI: 10.1099/00221287-114-2-313
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Recombination in Fused Spheroplasts of Providence alcalifaciens

Abstract: Spheroplasts of Providence alcalifaciens strain P29 auxotrophs were prepared by combined treatment with glycine and lysozyme-EDTA. About 15% of spheroplasts had areas of cytoplasmic membrane exposed where cell wall was absent. The spheroplasts of different auxotrophs were mixed pairwise and fusion was attempted with polyethylene glycol or nascent calcium phosphate. After spheroplasts had regenerated to bacterial forms selection was made for recombinants. Recombinants arose at frequencies of 3.8 x 10-6 to 1.7 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 22 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…To examine whether the prototrophic colonies are true fusants or not, the following experiment was conducted as a control. Approximately l0 9 vegetative cells/ml of the two strains were mixed, spread onto Raffinose-R medium, and cultured for 10 to 14 days; very small colonies appeared. This phenomenon seemed to be a result of the growth of the Z-6-C suc -strain in the presence of the Z-6-C frustrain; as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether the prototrophic colonies are true fusants or not, the following experiment was conducted as a control. Approximately l0 9 vegetative cells/ml of the two strains were mixed, spread onto Raffinose-R medium, and cultured for 10 to 14 days; very small colonies appeared. This phenomenon seemed to be a result of the growth of the Z-6-C suc -strain in the presence of the Z-6-C frustrain; as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, cell fusion could be regarded as a useful method for strain improvement. There have been many reports indicating protoplast fusion in Gram-positive bacteria such as Bacillus,S) Staphylococcus,6) Brevibacterium 7 ) and Streptomyces,S) but only a few on Gram-negative bacteria; for instance, Coetzee et al 9 ) have reported intraspecific fusion in Providence alcalifaciens, and Rastogi et aUO) in Mycobacterium aurum. Therefore, we decided to attempt spheroplast fusion in Z. mobilis, and obtained fusants at high frequencies.…”
mentioning
confidence: 99%
“…There have been manyreports indicating protoplast fusion in Gram-positive bacteria such as Bacillus^Staphylococcus, 6) Brevibacteriurn1) and Streptomyces^but only a few on Gram-negative bacteria; for instance, Coetzee et al 9) have reported intraspecific fusion in Providence alcalifaciens, and Rastogi et al10) in Mycobacterium aurum. Therefore, we decided to attempt spheroplast fusion in Z. mobilis, and obtained fusants at high frequencies.…”
mentioning
confidence: 99%
“…Preparation of protoplasts 8 Polyethylene glycol-induced protoplast fusion Genetic recombination by protoplast fusion has been described in several procaryotic species including Bacillus subtilis (Schaeffer et al, 1976), Bacillus megaterium (Fodor and Alfoldi, 1976) , Brevibacterium flavum (Keneko and Sakaguchi, 1979), Escherichia coli (Tsenin et al, 1979), Providence alcalifaciens (Coetzee et al, 1979), Staphylococcus aureus (Hirachi et al, 1979(Hirachi et al, , 1980Gotz et al, 1981), several Streptomyces spp. (Hopwood et al, 1977;Baltz, 1978;Godfrey et al, 1978), and lactic streptococci (Gasson, 1980).…”
Section: Protoplast Fusionmentioning
confidence: 99%
“…Dissolution of the peptidoglycan layers must be accompanied by removal of the outer membrane. In E. coli (Tsenin et al, 1979) and P. alcalifaciens (Coetzee et al, 1979) protoplasts were made by adding glycine to the culture medium and treating the washed cells with a combination of EDTA and lysozyme.…”
Section: Literature Review Chromosome Mapping In Staphylococcus Aureusmentioning
confidence: 99%